Language and Identity in Online Gamer Community - Malisi, Syabro; Suharsono, Suharsono; Setiawan, Slamet (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
The purpose of this study is to explain the relationship between language, identity, and community within online gamer community. This study specifically aims to explain 1) the difference in choice of words between groups, and 2) the implication of types of post in each group. The data were gathered through participant observation and interview. The groups chosen for this study were 4 Facebook groups from 3 online Japanese mobile games entitled Monster Strike, Puzzle and Dragon, and Brave Frontier due to their similarity. The analysis was done by comparing similar expression such as question and request. It was found that even though the game system is similar, each group has different ways to refers to the same thing, this at the same time also serves as group marker. Another finding is that each group has different perception towards particular element within their respective group and this can be analyzed from how they interact within their own group.